Programmed death ligand-1 protein expression difference in basal like and non-basal like triple negative breast cancer and its association with disease free survival and overall survival: A systematic review - Freda Halim; Hasrayati Agustina; Yohana Azhar; Bethy Hernowo (Oncology Reviews, 2021)
The study aims to summarize the literature and explore the strength of evidence for PD-L1 expression difference in basal like TNBC and non-basal like TNBC, and association of PD-L1 expression with disease free survival and overall survival in each group. A systematic search of the original research literature through November 29th, 2020, reported according to PRISMA guideline. Eligible studies investigated must have a primary outcome and at least one secondary outcome. Two reviewers independently searched, selected, and assessed quality of studies and risk of bias. Any discrepancies will be resolved by consensus or by consulting a third and fourth author. A total of 6813 articles were screened from which five articles were selected and assessed for quality of studies and risk of bias. Of 5 articles, no similar findings are found regarding the level of PD-L1 expression and its correlation with recurrence and overall survival. There is not enough substantial evidence to support the difference PD-L1 protein expression level in basal and non-basal like TNBC and its association with recurrence and overall survival. Hence, further studies are needed specifically to focus on this problem.